Liquid biopsy: an innovative and reliable method for detecting not only somatic, but also germline mutations in patients with colorectal and non-small cell lung carcinoma - Nelly Miteva-Marcheva; Hristo Ivanov; Veselin Popov; Gabriela Raycheva; Zhanet Grudeva-Popova; Vili Stoyanova (Biotechnology & Biotechnological Equipment, 2023)
Liquid biopsy is a non-invasive method of detecting cancer-related mutations from circulating cell-free DNA (cfDNA) and has emerged as a promising alternative to traditional tissue biopsies. However, its utility has so far been limited to the detection of somatic mutations in cancer cells. Our study examined germline mutations that are associated with pharmacogenetics in 19 patients diagnosed with colorectal cancer and 12 patients with non-small cell lung carcinoma, utilizing the highly advanced and non-invasive technique of liquid biopsy, followed by subsequent next-generation sequencing for comprehensive analysis. Despite the relatively modest sample size of patients under consideration, our results indicated a noteworthy correlation between the presence of adverse effects and the identified germline mutations. We have identified the following mutations with significant implications for pharmacogenetics: MTHFR c.1286A > C, MTHFR c.665C > T, DPYD c.2194G > A, DPYD c.85C > T, XPC c.2815C > A, UMPS c.638G > C, SLC22A2 c.808T > G, EGFR c.1562G > A, ABCB1 2677 T > G, GSTP1 c.313A > G, ERCC2 c.2251A > C, and SLC19A1 c.80A > G. In addition, we observed various adverse drug reactions in our patient cohort, encompassing myelosuppression, hepatotoxicity, neurotoxicity and gastrointestinal toxicity. Liquid biopsy has the potential to revolutionize cancer diagnosis and treatment by detecting both somatic and germline mutations. The preliminary results of studies on germline mutations are promising, but further research is needed to address the remaining challenges and to establish the utility of liquid biopsy as a reliable diagnostic tool for germline mutations.